Human and environmental justice in Guatemala - Henighan, Stephen, 1960-; Henighan, Stephen, 1960-; Johnson, Candace, 1971-; Johnson, Candace, 1971-; Deonandan, Kalowatie, 1958-; Lovell, W. George (William George), 1951-; Mack Chang, Helen; Maldonado, Lisa; Nolin, Catherine; Palacios, Rita M.; Paz y Paz Bailey, Claudia; Rey Rosa A., Magalí; et al. (University of Toronto Press, 2018)
"In 1996, the Guatemalan civil war ended with the signing of the Peace Accords, facilitated by the United Nations and promoted as a beacon of hope for a country with a history of conflict. Twenty years later, the new era of political protest in Guatemala is highly complex and contradictory: the persistence of colonialism, fraught Indigenous-settler relations, political exclusion, corruption, criminal impunity, gendered violence, judicial procedures conducted under threat, entrenched inequality, as well as economic fragility. Human and Environmental Justice in Guatemala examines the complexities of the quest for justice in Guatemala, and the realities of both new forms of resistance and long-standing obstacles to the rule of law in the human and environmental realms. Written by prominent scholars and activists, this book explores high-profile trials, the activities of foreign mining companies, attempts to prosecute war crimes, and cultural responses to injustice in literature, feminist performance art and the media. The challenges to human and environmental capacities for justice are constrained, or facilitated, by factors that shape culture, politics, society, and the economy. The contributors to this volume include Guatemalans such as the human rights activist Helen Mack Chang, the environmental journalist Magalí Rey Rosa, former Guatemalan Attorney General Claudia Paz y Paz, as well as widely published Guatemala scholars"--